Engineering the perfect croissant: A comprehensive study of processing variables and their impact on dough and final quality - Patranid Mutchadej; Naphatrapi Luangsakul (Applied Food Research, 2025)
• Optimal dough mixing time of 10 mins enhances croissant texture and volume. • Single-double folding yields crisp layers croissants with high sensory acceptance. • Proofing at 27°C for 2 hrs improves croissants ovenspring and butter flavor retention. • Convection ovens create crisp crusts croissant with consistent croissant quality. • Processing settings influence croissant structure, aroma, and consumer appeal. Precision processing is a key factor to produce the high-quality croissants, which is also essential for both artisanal and industrial production. This study systematically investigated the influence of key processing variables including dough mixing time, lamination techniques (number of laminated layers), proofing conditions, and oven type, on the physical, textural, and sensory qualities of dough and the final baked croissants. The dough could be reached optimal point after 10 mins of mixing, which enhances the dough’s resistance and elasticity, yielding croissants with an exquisite crumb structure, consistent shape, golden-brown crust, crisp texture, and rich buttery flavor. Following single-double folding (25 layers) and proofing at 27°C for 2 hrs, the dough showed enhancements in proofing, oven spring, volume, hardness, and luminosity. This improved the aroma and flavor of croissants, augmenting their sensory properties. Both convection and deck ovens produce acceptable products, but convection ovens yield in croissant with a more symmetrical shape, a crispier crust, and a more pronounced butter flavor. Principal component analysis (PCA) was utilized to categorize treatment effects and ascertain optimal processing settings, hence validating the previously mentioned findings. These findings provide insights into optimizing croissant production processes to achieve consistent product quality and enhanced consumer satisfaction.
Keywords: Food composition and properties; Polysaccharides Composition and Applications; Food Chemistry and Fat Analysis